Periodontal Disease And Its Association With Chronic Disease: A Literature Review - MEENAKSHI SREERAM; ADINATH SURYAKAR; NITIN DANI; SMITA KHEDKAR (International Journal of Pharma and Bio Sciences, 2012)
Background The aim of this article is to review various studies aimed at finding the association between Periodontitis and Chronic Kidney Disease. Methods A search was conducted for all the articles in the past that have studied the association between Periodontitis and Chronic Kidney Disease. Data sources primarily included Pub Med with MeSH terms and free text, Scopus and Cochrane library, Google Scholar and Copernicus. In addition, a hand search of selected periodontal journals and review articles was conducted. Result Almost all the work in this direction has developed in the last decade. Majority of the articles suggest a strong positive association between the two. Non-surgical Periodontal treatment seems to improve kidney functions in affected persons. A couple of studies, though, have found no associations between periodontal disease with alterations in kidney functions.